AB0551 Obstetrical morbidity related to anti-ssa antibodies: data from a french monocentric retrospective study. (12th June 2018) - Plaçais, L.; Carrat, F.; Carbillon, L.; Nicaise, P.; Benbara, A.; Fain, O.; Mekinian, A.
Abstract : Background: Obstetrical morbidity is an issue among autoimmune diseases patients. Anti-SSA positivity is well known for it's effect on fetus and risk of congenital heart block but no evidence has been yet found for its effect on obstetrical morbidity Objectives: To investigate anti-SSA positivity effect among a large monocentric cohort of obstetrical morbidity patients and to evaluate the efficacity of different treatment regimens Methods: All women who were seen from January 2010 to January 2015 in Jean-Verdier University Hospital for obstetrical morbidities were retrospectively included. All patients had been tested for anti-nuclear antibodies and anti-SSA/Ro and anti-SSB/La antibodies. Results: We included 244 women (median age 34 years [interquartile range 21–53]) with 869 pregnancies overall. In 27 (11%) patients with anti-SSA antibodies, the median age at the time of pregnancy was 29.5 (17–40) years, with mean number of 3.66 pregnancies per woman. For these 27 patients, 83/99 pregnancies (84%) had an adverse obstetrical outcome: fetal loss (n=65; at a median of 20 (4–38) weeks' gestation), preeclampsia (n=15), intrauterine growth restriction (n=7), prematurity (n=7), and congenital heart block (n=2). In comparing women with obstetrical antiphospholipid syndrome and unexplained adverse complications, there was no major difference in frequency of recurrent miscarriages, preterm deliveries, preeclampsia or fetal loss. Among factors associated with obstetrical outcome and fetal loss, aspirin and hydroxychloroquine treatments were significantly associated with a favourable obstetrical outcome: odds ratio 0.05 [95% confidence interval 0.01; 0.37] (p=0.003) and 0.15 [0.02; 0.98] (p=0.04). Conclusions: Women with unexplained recurrent obstetrical complications should be screened for anti-SSA antibodies. The benefit of aspirin and hydroxychloroquine treatment to improve the obstetrical outcome should be confirmed in prospective studies. Disclosure of Interest: None declared